Harmonizing Tradition and Sharia: Istishab in Managing a Deferred Non-Negotiated Fish Transactions in Indonesia - Amiruddin, Muhammad Majdy; Sulaeman, Budiman; Ahrar, Muhammad Rifki; Yusuf, Ahmad; Nusair, Abuyamen (Mazahibuna: Jurnal Perbandingan Mazhab, 2024)
This study aimed to analyze the application of Istishab, a tenet of Islamic jurisprudence, to address the issues of non-negotiated fish prices within the Iha community, Central Maluku, Indonesia. The community was characterized by complicated relationships between religious principles and cultural traditions, which frequently led to tension. The analysis addressed a significant issue which included the reconciliation of the centuries-old traditions of the community with the Sharia law to prevent disagreements and ensure the group's economic viability. Using in-depth interviews with stakeholders, detailed market observations, and thorough document analysis, this study investigated the social, financial, and normative dynamics of Istishab through a qualitative case study methodology. The results showed that Istishab stabilized prices, reduced conflicts, and supported the community's economic resilience by mediating between Islamic legal principles and cultural practices. This showed the adaptability of Islamic law in adopting and reinforcing local traditions. Furthermore, the study showed how Istishab served as a bridge between cultural and Sharia disputes. It concluded that Istishab provided a practical solution for maintaining harmony in economic transactions within multicultural communities. The results possessed broader implications for the integration of Islamic legal concepts with local practices to promote communal stability.